Gehenna . its monarch and inhabitants. A dissertation on the site, extent, and antiquities of the kingdom of Hell: embracing a great variety of information respecting its monarch, the nature, manners, and customs of its inhabitants; [...].; (Leeds, 1841)
Ingeb. bij: J.N. Bailey, Lycurgus.